Rifampicin Resistance in Primary Pulmonary Tuberculosis at HMC Hospital Peshawar Department of Pulmonology a Multi Center Study - Anwar Ul Haq, Muhammad Asif Khan, Imran Qadir Khattak, Farhan Zeb, Hameed Ullah, Muhammad Awais, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: According to estimates from the World Health Organization, TB afflicted about 12 million people in 2019 and claimed nearly 1.7 million lives. Pakistan is rated fifth worldwide for the prevalence of TB and fourth among developing nations for the emergence of treatment resistance. In Pakistan, there are around 525,000 new cases of TB each year, and 20,000 people develop medication resistance. A high mortality rate is caused by drug resistance. Before treating the patient for medication resistance and for a cure, it should be confirmed with a drug susceptibility test. Objective: To determine the prevalence of rifampicin resistance in patients with primary pulmonary TB using a drug susceptibility test. Methodology: In this Multi Center study, all patients who attended the pulmonology department of the HMC Hospital in Peshawar between 2018 and 2020 were included. The study comprised 296 smear-positive TB patients who attended the pulmonology department and had no prior history of ATT consumption. Further testing of the patient's sputum for rifampicin resistance and Mycobacterium TB was done using the PCR-based Gene Expert assay. Results: In the current study, 296 TB patients in total were included. According to our statistics, there were 200, 205, and 140 TB patients in the most recent three years 2018,19,2020, correspondingly (Figure 2). The study's participant population consisted of 157 men (52%) and 139 women (48%) (Table 1). The ratio of men to women was 01.11:12. 192 (64%) of the population lived in Peshawar, 33 (11%) in Khurram Agency, swat 25 (10%) and 45 (18%) in Charsadda (Figure 3). The findings revealed that Peshawar City was home to the bulk of the TB sufferers. 95 (07%) of the TB patients had extremely excellent socioeconomic standing, followed by 106 (36%) patients with average socioeconomic standing, and 166 (57%) patients with poor socioeconomic standing. Rifampicin resistance was found in 18 (06%) of these 296 TB patients (Table 2). It's important to note that 20 (60%) of the positive rifampicin resistance cases were in men and 13 (40%) were in women (Table 1). Additionally, the data we gathered indicated that rifampicin resistance was stronger in patients with low socioeconomic level (17%) and was lower in patients with high socioeconomic status (3%) for TB patients. Table 2. Conclusion: This study demonstrates a clear relationship between patient socioeconomic level and rifampicin resistance. Although TB is curable, a patient's chances of being cured are decreased and they become more resistant to other medications when they develop resistance to one or more treatments, particularly rifampicin. Keywords: Rifampicin, Tuberculosis,GeneXpertassay,drugsusceptibility.